Local thermal nonequilibrium effect on nanofluid filled porous cavity subject to mixed convection heat transfer. Issue 2 (9th September 2020) - Rajarathinam, M.; Chamkha, A. J.
Abstract: In this study, a numerical study is performed to determine the significance of local thermal nonequilibrium on mixed convection heat transfer of a copper water‐based nanofluid in an inclined porous cavity. By employing the nonequilibrium hypothesis, the governing equations for nanofluid flow in a porous medium are solved by the Semi‐Implicit Method for Pressure Linked Equation (SIMPLE) algorithm. From the obtained results, the nanofluid flow and thermal characteristics are analyzed through streamlines and isothermal plots whereas the heat‐transfer rate of the system is scrutinized via the average Nusselt number.